Institutional-based customer relationship management (CRM) solution: The implementation success factors - Jimoh, T.B.; Jimoh, R.G. (2010)
It has become imperative for students of higher institutions of learning to be well managed and handled so as to present a good image of the institution to the students.Higher institution of learning nowadays now consider their students as their customers and thereby work towards ensuring the maximum possible customer satisfaction level similar to what is applicable in the real business environment.Many authors have concluded that it is high time all higher institutions of learning embraced the use of Customer Relationship Management (CRM) solutions in monitoring student-institution relationships from the time of enrolment to the alumnus stage. This paper reports a quantitative study conducted in a Nigerian university environment to determine the critical success factors for implementing any institutional-based CRM solution. The implementation factors are identified in order of their importance.